Survey Training for Collecting Data of Nagari Tanjung Balik - Dina Fitria; Nonong Amalita; Syafriandi Syafriandi; Zilrahmi Zilrahmi; Admi Salma; Dodi Vionanda; Yenni Kurniawati (Pelita Eksakta, 2023)
Collecting data is the initial stage of data processing. Such that, it is needed to make sure the data collected is representative. Surveyor is one of its principal components. But, Nagari as a small component of a residence lack of professional surveyor for the work of the survey. The Statistics Department as a producer of statistician gives training to local residents to collect their own data using the right method in Nagari Tanjung Balik